The Study of Operational System in Tunnel Boring Machine (TBM) for Klang Valley Mass Rapid Transit (KVMRT) - Kori, Siti Nurnajihah; Abd Latif, Muhamad Faiz; Mok Wen Yao (Progress in Engineering Application and Technology, 2022)
The Tunnel Boring Machine (TBM) operator is always burdened with the workload to monitor and control the parameters to ensure the condition and position of the TBM are faultless. This research aims to study the autonomous system in TBM that can reduce the burden on the operator significantly and at the same time ensure that TBM can operate efficiently with an autonomous system. The observation and comparison data have been done in both manual and autonomous systems based on the data collected in the cloud data warehouse. The data shows the manual and autonomous systems in steering and face pressure operation. Finally, it can be seen that the autonomous system is able to steer and control the face pressure which the conventional TBM should apply to this autonomous system.